Extending Quantum Links: Modules for Fiber‐ and Memory‐Based Quantum Repeaters. Issue 11 (20th October 2020) - van Loock, Peter; Alt, Wolfgang; Becher, Christoph; Benson, Oliver; Boche, Holger; Deppe, Christian; Eschner, Jürgen; Höfling, Sven; Meschede, Dieter; Michler, Peter; Schmidt, Frank; Weinfurter, Harald
Abstract: Elementary building blocks for quantum repeaters based on fiber channels and memory stations are analyzed. Implementations are considered for three different physical platforms, for which suitable components are available: quantum dots, trapped atoms and ions, and color centers in diamond. The performances of basic quantum repeater links for these platforms are evaluated and compared, both for present‐day, state‐of‐the‐art experimental parameters as well as for parameters that can in principle be reached in the future. The ultimate goal is to experimentally explore regimes at intermediate distances—up to a few 100 km—in which the repeater‐assisted secret key transmission rates exceed the maximal rate achievable via direct transmission. Two different protocols are considered, one of which is better adapted to the higher source clock rate and lower memory coherence time of the quantum dot platform, while the other circumvents the need of writing photonic quantum states into the memories in a heralded, nondestructive fashion. The elementary building blocks and protocols can be connected in a modular form to construct a quantum repeater system that is potentially scalable to large distances. Abstract : Experimental building blocks for memory‐based quantum repeaters serving as modules to construct larger repeater systems for long‐distance quantum communication over optical fiber networks are considered. A small set of experimental parameters is identified to assess the performance of the repeater elements for three different platforms via secret key rates in quantum key distribution compared with channel links unassisted by quantum repeaters.